IMPLEMENTASI KEBIJAKAN KARTU INDONESIA PINTAR PADA JENJANG SEKOLAH DASAR (SD) DALAM UPAYA PEMERATAAN PENDIDIKAN DI DINAS PENDIDIKAN KOTA MEDAN - Fajar Siddik; Agnes Yohana Silalahi; Indri E Y Napitupulu; Zahwa Alya Azzahra Nst; Putri Nurul Afifah Bangun; Hannah Selly Melinda Sagala; Franklin Asido Rossevelt (Histeria Jurnal: Ilmiah Soshum dan Humaniora, 2022)
This study aims to determine the implementation of the Smart Indonesia Program (PIP) through the Smart Indonesia Card (KIP) policy in Medan City. Through this policy, researchers analyze whether educational equity can be achieved with the program. The research method used in this research is descriptive research method using a qualitative approach through research data in the form of words and quotes from interviews and secondary data, namely collecting several literature sources. The result is that the Smart Indonesia Card assistance program has so far been right on target. However, there are still violations committed by irresponsible persons. The Education Office as the coordinator in the implementation of the provision of KIP assistance as much as possible and as firmly as possible to continue to oversee the implementation of the provision of this assistance to every elementary school student who has been registered as a recipient of KIP assistance.